Postoperative pain management in the postanesthesia care unit: an update - Luo J; Min S (Journal of Pain Research, 2017)
Jie Luo, Su Min Department of Anesthesiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China Abstract: Acute postoperative pain remains a major problem, resulting in multiple undesirable outcomes if inadequately controlled. Most surgical patients spend their immediate postoperative period in the postanesthesia care unit (PACU), where pain management, being unsatisfactory and requiring improvements, affects further recovery. Recent studies on postoperative pain management in the PACU were reviewed for the advances in assessments and treatments. More objective assessments of pain being independent of patients’ participation may be potentially appropriate in the PACU, including photoplethysmography-derived parameters, analgesia nociception index, skin conductance, and pupillometry, although further studies are needed to confirm their utilities. Multimodal analgesia with different analgesics and techniques has been widely used. With theoretical basis of preventing central sensitization, preventive analgesia is increasingly common. New opioids are being developed with minimization of adverse effects of traditional opioids. More intravenous nonopioid analgesics and adjuncts (such as dexmedetomidine and dexamethasone) are introduced for their opioid-sparing effects. Current evidence suggests that regional analgesic techniques are effective in the reduction of pain and stay in the PACU. Being available alternatives to epidural analgesia, perineural techniques and infiltrative techniques including wound infiltration, transversus abdominis plane block, local infiltration analgesia, and intraperitoneal administration have played a more important role for their effectiveness and safety. Keywords: postoperative complications, anesthesia recovery period, pain assessment, pain management, acute pain